'Adālah Maqāṣhidi Resolution and Gen-Z Perspective on Human Rights Discrimination of Indonesian Migrant Workers in Malaysia - Basid, Abdul; Abdul Adzim; Lilik Nur Kholidah; Amrulloh Amrulloh; Titi Mutiara Kiranawati; Nor Surilawana Sulaiman (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study investigates the contributions of Gen-Z perspectives and the ‘Adālah Maqāṣhidi Resolution in addressing human rights discrimination against Indonesian migrant workers in Malaysia. Two central questions are explored: how young Indonesians perceive and support migrant-worker protection, and how maqāshid-based justice can inform a rights-protective policy ethic. Utilizing a qualitative descriptive-exploratory design, the research integrates an online survey of over 280 Gen-Z respondents aged 18–21, selected for their engagement with migrant-worker or human rights issues, alongside in-depth interviews, literature analysis, and a transcript-based review of the 2025 shooting case involving five Indonesian migrant workers in Malaysian waters. The findings reveal that respondents recognize migrant workers as a legally and socially vulnerable group, express strong concern for state responsibility, media advocacy, and human rights education, and identify digital platforms as strategic spaces for public pressure, although concrete participation varies. The analysis further demonstrates that ‘Adālah Maqāṣhidi provides a normative bridge between Islamic legal justice, human dignity, and migrant-worker protection by emphasizing equality before the law, prevention of harm, and public welfare. This study offers an integrated framework that links youth-based digital advocacy, transnational labor protection, and Islamic justice ethics and recommends stronger bilateral safeguards, rights literacy, and inclusive legal protections for both documented and undocumented workers